SOSIALISASI PENTINGNYA MAKANAN BERGIZI DAN POLA HIDUP SEHAT UNTUK MENCEGAH STUNTING DI DESA SUMBER PINANG KEC. MLANDINGAN KAB. SITUBONDO - Auliya Gaffar Rahman; Lailatul Rahmawati; Widhya Putriana; Faize Turrofida (Yayasan Bakti Cendekia Nusantara, 2026)
Stunting is a chronic nutritional problem that remains a concern in Indonesia because it impacts children's physical growth and cognitive development. One preventative measure is to increase public knowledge about the importance of nutritious food and a healthy lifestyle. This activity aimed to provide outreach to the community in Sumber Pinang regarding the importance of balanced nutrition and healthy lifestyles in preventing stunting. The method used was a demonstration through a presentation using an LCD projector, followed by a question-and-answer session and a quiz to evaluate participants' understanding. The target group was the village community, particularly mothers and parents of toddlers. The results showed that participants were very enthusiastic about participating in the outreach, and there was an increase in public understanding regarding the importance of balanced nutrition and adopting a healthy lifestyle. This was evident in the participants' active participation in the discussion and their ability to answer questions. In conclusion, this outreach activity was effective in increasing public knowledge and awareness as a means of preventing stunting. Therefore, similar activities need to be conducted continuously to achieve more optimal results.